Dispersion stability of Si3N4 nano-particles modified by γ-methacryloxypropyl trimethoxy silane (MAPTMS) in organic solvent. Issue 1 (January 2015) - Cheng, Guojun; Qian, Jiasheng; Tang, Zhongfeng; Ding, Guoxin; Zhu, Jinbo
Abstract: Silicon nitride nano-particles (nano-Si3 N4 ) were modified by grafting commercial γ-methacryloxypropyl trimethoxy silane (MAPTMS) via a direct blending method in solution. The changes and dispersion stability in the nano-Si3 N4 were determined using different techniques. Compared with the native nano-Si3 N4, the modified nano-Si3 N4 showed more stable colloidal dispersion in ethyl acetate. Results of the thermogravimetric analysis (TGA) indicated that the MAPTMS molecules were absorbed or anchored on the surface of nano-Si3 N4 particles, which facilitated to hinder the aggregation of nano-Si3 N4 particles. The hydroxyl groups on the surface of nano-Si3 N4 could interact with silanols groups [SiOCH3 ] of MAPTMS and the formed covalent bands [SiOSi] were testified by Fourier transform infrared spectra (FTIR). The MAPTMS can be combined with nano-Si3 N4 by covalent bonds, thereby changing the surface properties of nano-Si3 N4 and enhancing dispersion in organic media. Nano-Si3 N4 particles modified by MAPTMS could be used for polymer blends, thermoplastic elastomers and polymer nanocomposites with better performance and longer life cycle.